2012
DOI: 10.1002/atr.1200
|View full text |Cite
|
Sign up to set email alerts
|

A method to estimate the historical US air travel demand

Abstract: The complete historical US air travel demand is not available to the general public. In this paper, we propose a route-based optimization model to estimate the historical US air travel demand. We show that the distribution of estimated demand follows a logit model. An iterative solution algorithm is proposed to solve the optimization model. The route utility is designed as a function of route characteristics. A feedbackadjustment scheme is proposed to estimate the model coefficients in the route utility functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…At each iteration, the solution algorithm maximizes the duality of the original problem sequentially along unit directions, and keeps some optimality conditions satisfied for the original problem. The same idea has been adopted to design solution algorithms for the traffic assignment problem in Bell (1995b) and the demand estimation problems in Bell et al (1997), Nie et al (2005), Chen et al (2010), and Li et al (2013). Especially, the numerical examples in Chen et al (2010), Li et al (2013), and Tang and Zhang (2013) show that this type of solution algorithms is efficient for large-size networks.…”
Section: A Bi-level Model To Estimate the Us Air Travel Demandmentioning
confidence: 95%
See 3 more Smart Citations
“…At each iteration, the solution algorithm maximizes the duality of the original problem sequentially along unit directions, and keeps some optimality conditions satisfied for the original problem. The same idea has been adopted to design solution algorithms for the traffic assignment problem in Bell (1995b) and the demand estimation problems in Bell et al (1997), Nie et al (2005), Chen et al (2010), and Li et al (2013). Especially, the numerical examples in Chen et al (2010), Li et al (2013), and Tang and Zhang (2013) show that this type of solution algorithms is efficient for large-size networks.…”
Section: A Bi-level Model To Estimate the Us Air Travel Demandmentioning
confidence: 95%
“…(1)) seems to have little physical meaning, it is designed in a way that, in the optimal solution, the estimated demand distributes according to a logit model. Using the first-order optimality condition (i.e., Karush−Kuhn−Tucker (KKT) condition) (Bazaraa et al, 2006), Li et al (2013) showed that:…”
Section: ) Andmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods could produce relatively accurate and cost-beneficial estimates [10,23]. It is worthwhile to point out that models that utilize posterior observations have also been developed to estimate the historical demand in commercial air transportation (see, e.g., Li et al [24]; Li and Baik [25]; Li [26]; Li et al [27]; and Li [28]) and ground transportation (see, e.g., Maher [29]; Cascetta [30]; Bell [31]; Yang et al [32]; Codina and Barceló [33]; Chootinan et al [34]; Doblas and Benitez [35]; Nie et al [36]; Lundgren and Peterson [37]; Chen et al [38]). …”
Section: Introductionmentioning
confidence: 99%